Emotional intelligence and its implication towards job satisfaction / Hamim Senin - Senin, Hamim (Faculty of Business and Management, 2010)
Nowadays in locally our beloved country, there is less number of researches about emotional intelligence. It would be valuable and interesting to have more current research on emotion intelligence due to the rapid change of culture and environment of any organization or sector. The purpose of this paper is to analyze the relationship between emotional intelligence (EI) and job satisfaction by considering any other factors that might be influence the emotional intelligence. The spot question or main objective of the study is to analyze the effect of emotion intelligence and job satisfaction itself, thus taking the consideration on how respondent’s feeling through their work, and recognize the relationship between job post and job satisfaction. The data use in this study was gathered from two method of collecting data, which is primary data and secondary data. Respondents have been given 4 pages of questionnaire with the total number of 56 questions, in order to gather information regarding the purpose of the study. Hence, 40 questionnaires successfully answered and the data were compute by using Statistical Program for Social Science (SPSS). The result indicates that, there is no significant relationship between emotional intelligence itself and job satisfaction.